Empire's backyard - Baral, K. C., 1954- author. Link
1 online resource (258 pages)
Keywords: This book transcends traditional historical analysis to explore the intricate tapestry of colonialism, modernity, and identity formation in Northeast India. Moving beyond a simplistic view of the region as the British Empire's 'backyard,' it examines the transformative processes that turned Northeast India beyond Sylhet, the empire's eastern outpost, into a vibrant frontier. While recognizing the importance of exploration and territorial expansion in establishing colonial dominance, the narrative emphasizes the crucial roles of resistance and local agency in shaping the region's history.The volume critically analyzes the influence of the Church as a powerful force within the 'civilizing mission,' alongside military interventions. It dissects the complex relationship between colonialism and modernity, revealing how the rhetoric of progress often concealed motives of resource extraction and cultural disruption. Through a meticulous unraveling of structures, systems, and processes, the work weaves a compelling narrative of Northeast India, not as a passive recipient of colonial ideas, its imposition of alien rules and values but as a region actively shaped by the interplay of power, resistance, and adaptation.This book will be of interest to scholars, researchers, and students of history, sociology, colonial and postcolonial studies, cultural studies, and South Asian studies, especially those concerned with Northeast India.